ANALISIS STRUKTUR DAN NILAI MORAL DALAM NOVEL SI LAMSIJAN KAEDANAN KARYA KI UMBARA - Muhamad Aldiansah; Ratnawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The aim of this research is to describe the structure and moral values ​​contained in the novel Si Lamsijan Kaédanan by Ki Umbara with an analysis of the structure and moral values. This research is qualitative research using qualitative descriptive methods. The research technique used is a literature review technique. The instrument used in this research was a data card. The first result of this research is the structure in the novel Si Lamsijan Kaédanan and the second is the moral ajén in the novel Si Lamsijan Kaédanan. The theme in this novel is about love and infatuation; The plot used in this story is a mixed plot; There are 15 perpetrators in this novel; The settings contained in this novel include 99 settings; the title of the novel Si Lamsijan Kaédanan refers to the main character, namely Si Lamsijan; The point of view used in this novel is third person unlimited; there are 4 language styles and 43 tones; 59 symbolism; and this novel includes dramatic irony. third, there are 19 moral values ​​contained in the novel, including 4 human morals towards God, 3 human morals towards oneself, 9 human morals towards other humans, 1 human moral towards time, and 2 human morals in the pursuit of outer and inner satisfaction. The output of this research is to produce articles published in national journals.